The Effect of Aloe vera and Chlorhexidine as Disinfectants on the Success of Selective Caries Removal Technique: A Randomized Controlled Trial - Al-Abdullah, Ahmad; Edris, Samer; Abu Hasna, Amjad [UNESP]; Carvalho, Lara Steffany de; Al-Nahlawi, Talal (Wiley, 2022)
This study aimed to evaluate the effect of Aloe vera and chlorhexidine CHXas disinfectants on the success of selective caries removal technique in deep carious lesions. A total of 60 patients with: (I) deep class II carious lesion diagnosed with reversible pulpitis; (II) good oral hygiene; (III) no gingival recession or periodontal diseases; (IV) no antibiotic or antifungal treatment in the last three months; and (V) no systematic disease or pregnancy were included in the study. Sixty patients were distributed randomly to three experimental groups (n = 20): Group 1: no disinfectant solution was applied (control group); group 2: the cavity was filled with 2% CHX for 5 mins and then dried with a sterilized cotton pellet; group 3: the cavity was filled with Aloe vera extract for 5 mins and then dried with sterilized cotton pellet. One week later, only teeth with vital pulp characteristics were restored definitely with resin composite. After 18 months, clinical and radiographic examination was performed by using a blinded separated evaluator. The data were tabulated and analyzed using the chi-square test by SPSS 13.0 with a significance level (p≤0.05). It was observed that 13 teeth of the control group, 14 teeth of the CHX group, and 16 teeth of the Aloe vera group were diagnosed with healthy vital pulp after 18 months. There was no significant difference between the CHX and the control group; however, there was a significant difference between the Aloe vera and control group (p≤0.007). Aloe vera extract as a cavity disinfectant increases the success rate of selective caries removal technique of deep carious lesions.